Appointed or Elected? How Mayoral Accountability Impacts the Provision of Policing - Andrea Colombo; Ilan Tojerow (Institute of Labor Economics (IZA), 2020)
This paper studies how the system by which mayors are elected impacts mayoral accountability and their provision of public goods. To do so, we analyze policing and crime incidence under mayors directly elected by voters and under mayors appointed by an elected body. Our identification strategy exploits a natural experiment provided by the introduction in 2005 of direct mayoral elections in the municipalities of one region of Belgium, Wallonia. Estimating a difference-in-differences model with a rich dataset registering locally-reported crimes from 2000 to 2012, our results show a post-reform decrease in overall crime between 4.9% and 5.7%, depending on the specification. Our results further suggest that more accountable mayors prefer fighting certain type of crimes more intensely, rather than increasing police efficiency overall. Lastly, our results show that the post-reform benefits we observe dissolve when the management of local police has to be coordinated among neighboring mayors, especially if they come from different political parties.
Keywords: D72; H10; K14; K40; 330; electoral accountability; crime; mayoral election; police